High Carbon Load in Food Processing Industrial Wastewater is a Driver for Metabolic Competition in Aerobic Granular Sludge - Paulo, Ana M. S.; Amorim, Catarina L.; Costa, Joana; Mesquita, Daniela P.; Ferreira, Eugénio C.; Castro, Paula M. L. (Frontiers in Environmental Science, 2021)
Aerobic granular sludge (AGS) processes are among the most robust wastewater treatments. One of their greatest advantages is related to the granules multi-layered structure, which creates a protective barrier against organic shock loads and variable wastewater composition, particularly attractive for the treatment of industrial wastewater. However, when treating a wastewater with variable and complex composition, the difficulty in identifying factors that most affect a specific biological process increases. In this study, the effect of OLR, namely carbon content, on nitrification in an AGS process treating fish canning wastewater was investigated. Besides process performance, also biomass morphological and structural changes and microbial community composition were analysed. Reactor operation lasted for 107 days and was divided in three phases during which different OLR and C/N ratios were applied. A higher OLR was applied during the first two phases (ca. 1.1 and 1.5 kg COD m-3 day-¹, respectively) compared to the third phase (between 0.12 to 0.78 kg COD m-3 day-1) and the C/N ratios also varied (ca. 4.4, 7.8 and 2.9, respectively). Throughout the operation, COD concentration in the outlet was lower than 100 mg O2 L-1. Nitrification was inhibited during the second phase and recovered afterwards. Principal component analysis (PCA) of quantitative image analysis and performance data indicated a loss of biomass robustness during the first two phases, recovering during the last phase. The AGS microbiome reached a stable composition by the end of the higher OLR period, until the end of operation. The main microbial diversity shifts were mostly associated to adaptation to higher or lower carbon availability. Bacteria and inferred enzymes associated to nitrogen and phosphorous removal were identified. Among the different identified EPS producers, Chryseobacterium was able to enrich and become dominant over operation. Despite the complexity of the fish canning wastewater, carbon was identified as the main driver for nitrification inhibition, while promoting changes in the physical characteristics and on the microbial community of granules.